Effects of an Urban Home Gardening Program on Plant Diversity and Home Garden Structure in Malang City, Indonesia - Erona Wafaretta; Riyan Riyadlun Najih; Amaliah Amriani Amran Saru; Muh. Syaiful Akbar (International Journal of Science and Environment (IJSE), 2026)
Residential home gardens are important components of urban green spaces that contribute to biodiversity conservation, food security, and public health. This study examined the effects of an Urban Home Gardening Program on home garden structure and plant diversity in Malang City, Indonesia. A total of 95 households were surveyed, comprising participants in the government program (JGP) and non-participants (NJGP). Data on home garden typology, plant composition, abundance, and plant diversity were analyzed using descriptive statistics, chi-square tests, and independent-samples t-tests. Three home garden types were identified: ground, mixed, and vertical/rooftop. Mixed gardens predominated among JGP households (48%), whereas ground gardens were more common in NJGP households (56%). Ornamental plants were the dominant plant group, followed by vegetables, fruits, medicinal plants, tubers, and staple food crops. JGP households maintained significantly higher plant diversity (13 vs. 8.4 varieties; p < 0.05) and a greater proportion of medicinal plants (59% vs. 32%; p = 0.013) than NJGP households. These findings indicate that the Urban Home Gardening Program primarily enhances plant diversity and promotes multifunctional home gardens rather than simply increasing plant abundance. The program therefore has considerable potential to strengthen urban biodiversity conservation, household food security, and the sustainable use of medicinal plants.